Analysis of Environmental Approval in Government Regulation No. 22 of 2021 on the Implementation of Environmental Protection and Management - Ningsih, Dwi Elvia; Frinaldi, Aldri; Rembrandt, Rembrandt (Universitas Negeri Padang, 2024)
The environment is one of the sectors that has undergone a transformation since the Job Creation Law was passed. A number of clauses in Law No. 32/2009 were removed and amended by the Cipta Kerja Law. One of them is the elimination of Environmental Permits and replaced with environmental approvals that are integrated with business licensing. Government Regulation No. 22 of 2021 on the Implementation of Environmental Protection and Management is a derivative regulation of the Cipta Kerja Law. Many stakeholders are still unaware of the government regulation even though it has been in effect for two years. Therefore, the purpose of this article is to provide a brief explanation of how environmental approvals are issued. The method is normative legal research through a literature study of the mechanism for issuing environmental approvals listed in Government Regulation No. 22 of 2021. This research uses content analysis and flow charts as analysis techniques. The mechanism for issuing environmental approval has been regulated in detail in Government Regulation No. 22 of 2021 starting from self-screening by the person in charge of the business and/or activity, preparation of environmental documents, the process of examining and/or assessing environmental documents in the form of Environmental Impact Analysis (EIA) and Environmental Management Efforts and Environmental Monitoring Efforts (UKL-UPL) forms and Issuance of Environmental Approval.